RESULTS OF POSTERIOR MYECTOMY FOR THE TREATMENT OF CHILDREN WITH CHRONIC CONSTIPATION - PEYVASTEH,Mehran (2015)
Background and Objectives - The aim of this study was to evaluate the result of posterior myectomy in children with chronic constipation who underwent to this surgery. Methods - Forty eight children with chronic constipation who did not respond to diet, laxative, or enema were included. Children with abnormal barium enema showing transitional zone were excluded. Children with documented metabolic disease diabetes, and hypothyroidism were also excluded. All patients underwent posterior myectomy. Children were followed during 1 year after surgery regarding frequency of fecal evacuation, fecal consistency, straining during defecation, and diameter of feces. Data was analyzed using SPSS version 13.0 (Chicago, IL, USA). Results - Of 48 cases that underwent surgery, 21 were male and 27 were female. Age range was 1.5 to 11 years old. Mean duration of constipation before surgery was 22.79±17.08 (range 6-48 months). Mean duration of medical treatment was 14.90±10.31 (range= 6-48 months). Fecal consistency, feces diameter, number of bowel movements and straining during defecation were compared before and after surgery. The results were statistically significant ( P <0.001). Of all cases, 52% continued treatment of constipation after surgery for 1 year. Ganglion cells were absent in 32 cases. Ganglion cells were present in seven children. Proximal ganglion cell was found in nine cases Treatment response was not different between cases according to status of ganglion cell in biopsy. Conclusion - Fecal consistency, feces diameter, number of bowel movements, and straining for defecation were improved after posterior myectomy. Another study with more sample is required for better evaluation of treatment.